Human Capital Deployment and Organizational Efficiency: A ‎Cross-National Benchmarking Analysis of Global Workforce Distribution Patterns - Kamanli, Ayse İlgün and Balcıoğlu, Yavuz Selim (International Journal of Accounting and Economics Studies, 2025)
The research examines human capital deployment strategies between different organizational sizes and geographic locations by analyzing ‎workforce distribution patterns across 8,395 global companies. The study uses Resource-Based View and Human Capital Theory ‎and Strategic Human Resource Management to analyze human capital as both a cost center and performance driver. The study incorporates ‎Institutional Theory and Contingency Theory , and Dynamic Capabilities to understand organizational adaptability and contextual influences. The research uses a quantitative cross-sectional design to study the connections between workforce size and market capitalization ‎and geographic origin, and sectoral distribution. The research demonstrates major differences in human capital efficiency between different ‎organizational sizes and geographic areas, and industrial sectors, which proves that standardized HR strategies are insufficient ‎and organizations need customized workforce scaling methods. The research advances human capital economics theory while providing practical guidance for global HR benchmarking and strategic workforce design‎.